Chemical Compositions of Dew and Scavenging of Particles in Changchun, China - Yingying Xu; Hui Zhu; Jie Tang; Yingzi Lin (Advances in Meteorology)
Dew and rain water were collected during 2013 and 2014 in Changchun, China. The dew was analyzed and the following parameters were measured: pH, EC, TDS, major anions (F−, Cl−, SO42-, and NO3-), and major cations (NH4+, Na+, K+, Ca2+, and Mg2+). The mean pH, EC, and TDS values of dew were comparable with the values for rainwater. The pH values of dew and rain were 6.72 and 6.16, respectively. Both EC (308 μS/cm) and TDS (154 mg/L) of dew were higher than those in rain samples. The concentration of main ions in dew was 1.5–5.7 times higher than levels in rainwater. The near-neutral pH values in dew were caused by the neutralization of acidity and buffering by the alkaline elements of soil origin (Ca2+). This neutralization was confirmed by a strong correlation between the acidic ions (SO42- and NO3-) and the major cations (Ca2+ and Mg2+). Natural dust made an important contribution to the ions present in dews, but the presence of sulfate concentrations that are notably higher than rain water (up to 1584.5 μeq/L) indicated a significant contribution of anthropogenic sources. Dew has the ability to capture particulates, and the purifying effect on the underlying surface was obvious.